Introduction of an educational robotics-based numeracy literacy corner - Putra, Yudi Yunika; Hendrik, Maulina; Rahmadi, Imam Fitri (Community Empowerment, 2025)
Mathematical literacy skills are crucial for solving everyday mathematical problems. However, at SD Muhammadiyah Pangkal Pinang, students' numeracy literacy skills are still relatively low. This condition is exacerbated by the absence of a dedicated numeracy literacy learning center and the limited skills of teachers in designing and developing such resources. This community service (PkM) activity aimed to introduce a numeracy literacy corner to teachers as an initial step towards establishing a more comprehensive learning center. The implementation method for this PkM included three stages of socialization: pre-activity, concept introduction, and evaluation. The results showed that teachers gave positive feedback on the numeracy literacy corner, considering it more engaging than conventional reading corners. It is hoped that this initiative can serve as a foundation for the optimal realization of a numeracy literacy learning center in the classroom in the future.